Psychological TV-series as a Phenomenon of the Consumer Society of the XXI Century - D. V. Prokofieva (Дискурс)
Introduction. The article examines modern psychological television series as one of the ways to satisfy the thirst for consumption and the desire to find meaning. The author considers the consumer society and the thirst for consumption as its integral characteristic and habit of a person in modern society. To analyze this phenomenon, the author turns to the works of philosophers, finding confirmation of their concepts in modern reality. The emphasis is on the fact that the objects of consumption are “objects” belonging to both material and spiritual culture, with the peculiarity that in the consumer choice itself there is no reflection as its basis. The subject of the research is the phenomenon of modern psychological TV-series.Methodology and sources. To analyze the phenomenon of psychological television series in the context of modern mass and popular culture, the author uses the method of phenomenological analysis, the method of historical parallels, the value method, the dialectical method. The article uses an interdisciplinary and comparative approach. The author relies on the work of representatives of these philosophical trends – Karl Marx, Erich Fromm, Alvin Toffler, Jean Baudrillard, Victor Frankl and others.Results and discussion. We can name many reasons why people can watch TV-series, for example, taking a break from routine, a desire to relax, this is a certain way of spending leisure time. Our goal was to analyze TV-series as a phenomenon of a consumer society, and the situation when watching the series is a goal in itself and a kind of escapism, a way to escape from reality and filling your time. The task was to identify the natural and social reasons for the popularity of modern psychological series.Conclusion. As a result of the analysis, the author concluded that modern high-quality television series perform a triune task. On the one hand, they captivate the plot and allow you to relax and relieve stress, avoiding strong concentration. On the other hand, they involve a claim to be intelligent. And the third point – they distract from routine and everyday life while eliminating the need for a daily choice of a way of spending leisure time. TV-series are a product of the consumer society, and therefore the prerequisite for reflection contained in them is far from always being realized. As a result, the series itself becomes for a person just another way to spend their own time and fill the inner emptiness.